RANCANG BANGUN MESIN PENGADUK SABUN CUCI CAIR UNTUK MENGOPTIMALKAN WAKTU PRODUKSI PADA INDUSTRI RUMAH TANGGA - Rahmatul Ahya; Rian Prasetyo; Maria Puspita Sari; Mathilda Sri Lestari (Politeknik Meta Industri, 2021)
Indonesia's economy during the second quarter of 2020 getting a contraction about 4.19 percent, due to the COVID-19 pandemic. This decline has an impact on the economic sector, one of which is MSMEs which contribute 15.75 percent annually to economic growth. Liquid soap is one of the MSMEs products that needs improvement because of this impact. This research was purposed to develop the process of mixing liquid soap ingredients with an electric-powered stirrer machine to obtain a constant mixing process, and produce a homogeneous mixture of liquid soap. The results of this research succeeded in making a liquid soap mixer machine using “L” shape plate frame with dimensions of length x width x height about 610 x 530 x 900 mm. The power of the stirrer machine about 0.25 HP using an electric motor, with rotation speed of 1400 rpm on electric motor and 343.4 rpm on stirrer, and produces a torque for stirring the concentrate of liquid soap about 3.42 N.m. The results of the production of liquid soap with the machine show an increased in production time about 30.9%, and the product have characteristics of a thicker liquid soap, than manual production, for the same production volume.